CYP2S1 and CYP2W1 expression is associated with patient survival in breast cancer. (28th July 2022) - Aiyappa‐Maudsley, Radhika; Storr, Sarah J; Rakha, Emad A; Green, Andrew R; Ellis, Ian O; Martin, Stewart G
Abstract: The cytochrome P450 family of enzymes metabolise a wide range of compounds and play important roles in breast cancer pathogenesis due to their involvement in estrogen metabolism and the production of carcinogenic metabolites during this process. The orphan CYPs, CYP2S1, and CYP2W1 are reportedly upregulated in breast cancer. However, their expression and association with clinicopathological and survival parameters have not been previously assessed in a large cohort of breast cancers. Protein expression of CYP2S1 and CYP2W1 was assessed in early‐stage invasive breast cancers ( n  = 1, 426) using immunohistochemistry and correlated with various clinicopathological parameters and survival. mRNA expression of CYP2S1 and CYP2W1 was also assessed in the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) cohort. Low nuclear and cytoplasmic CYP2S1 was significantly associated with high‐grade tumours ( p  ≤ 0.009), intermediate Nottingham prognostic index (NPI) group ( p  ≤ 0.025), high mitotic frequency ( p  ≤ 0.002), human epidermal growth factor receptor 2 (HER2)‐negative disease ( p  ≤ 0.011), and ductal carcinoma ( p  ≤ 0.022). Cytoplasmic CYP2S1 was additionally associated with patients ≥50 years ( p  < 0.001), estrogen receptor (ER)‐positive tumours ( p  = 0.011), and high nuclear pleomorphism ( p  = 0.003). Low cytoplasmic CYP2W1 was significantly associated with patients ≥50 years ( p  = 0.002), HER2‐negative disease ( p  = 0.003), intermediate NPI ( p  = 0.013), and mitosis ( p  = 0.009). Low cytoplasmic CYP2S1 was significantly associated with adverse breast cancer specific survival ( p  = 0.034), which remained so in multivariate analysis (hazard ratio [HR]: 0.639; 95% confidence interval [CI]: 0.483–0.846; p  = 0.002). Low nuclear CYP2W1 was significantly associated with adverse breast cancer specific survival ( p  = 0.012), with significance also maintained in multivariate analysis (HR: 0.677; 95% CI: 0.510–0.898; p  = 0.007). No associations with survival were observed in the METABRIC cohort. CYP2S1 and CYP2W1 are associated with patient survival in breast cancer and may be important prognostic biomarkers.